Galeni In Hippocratis Epidemiarum librum II Commentariorum I-III versio Arabica - Swain, Simon; Vagelpohl, Uwe (2016)
This volume offers the first critical edition of the Arabic translation of Galen's Commentary on Book 2 of the Hippocratic Epidemics. It follows the edition of Galen's Commentary on Book 1 published previously in this series. The Arabic text is accompanied by an English translation and extensive indices. The introduction outlines the history of the Greek and Arabic text and discusses the authorship, dating, and style of the Arabic translation.